Inflammatory Responses to Salmonella Infections Are Serotype-Specific. (16th September 2013) - Ktsoyan, Zhanna; Ghazaryan, Karine; Manukyan, Gayane; Martirosyan, Anush; Mnatsakanyan, Armine; Arakelova, Karine; Gevorgyan, Zaruhi; Sedrakyan, Anahit; Asoyan, Ara; Boyajyan, Anna; Aminov, Rustam
Abstract : The main purpose of this study was to investigate the profile of inflammatory response in patients with acute salmonellosis caused by two serotypes of Salmonella enterica, S. Enteritidis and S. Typhimurium, as well as in convalescent patients with previous acute disease caused by S. Enteritidis. Patients with acute disease showed significantly elevated levels of IL-1 β, IL-17, IL-10, and calprotectin compared to healthy control subjects. In convalescent patients, these markers were also significantly elevated, with the exception of IL-1 β . Multivariate statistical analyses with the use of these variables produced models with a good predictive accuracy resulting in excellent separation of the diseased and healthy cohorts studied. Overall, the results suggest that the profile of inflammatory response in this disease is determined, to a significant degree, by the serotype of Salmonella, and the profile of certain cytokines and calprotectin remains abnormal for a number of months following the acute disease stage.